Do life- or school-satisfaction and self-esteem indicators explain the oral hygiene habits of schoolchildren? - Honkala S, Honkala E, Al-Sahli N. (Blackwell Synergy, 2007)
The aim of this study was to ascertain how frequently toothbrushing and flossing are practiced among schoolchildren in Kuwait and whether life- and school-satisfaction and self-esteem indicators are associated with oral hygiene habits.